Factors Influencing Local Opposition Towards Housing Development - Kheng, Sok Yee (2021)
Residential housing is dominant properties in Malaysia’s real estate market. Residential properties refer to a property designated for house or home where people live in. The house is a place provides comfort, security, shelter and dignity, a natural framework for realizing, economic, social, enriching and integrating and culture resources. Local opposition became an obstacle for developer to carry on the development including obtaining authority’s approval from various parties as well as sale affection. This study background is to mainly identify the reason and behaviour of the local opposition parties towards housing development on the case study of a housing development project located in Jalan 21/19a, Petaling Jaya. The methodology research design for the purpose to relate the research questions to the data analysis. Because the goal of this study is to determine the relationships between local residents' perceptions of housing development procedures, the most appropriate research tool to use is a quantitative approach employing a self-administered questionnaire survey. The SPSS software was used in this study for fabricate the result. Therefore, the result of hypothesis shows positive. Finally, Local residents’ opposition direct impact the attitudes toward local housing project. As a result, main purpose of this study was to offer essential input to the Malaysian government and the Secretary of Selangor Government (Housing Division) in order to provide more high-quality public local housing to low-income people who cannot afford to buy a property on the open market.